Control Variable Parameterization-based Optimization of Clinical Drug Scheduling for Cancer Chemotherapy with Daily Treatment - Xiao, Qi; Liu, Ping (Chinese Automation Congress (Online), 2022)
With the deepening of research on the combination of cancer chemotherapy and optimal control theory, the consistency between theoretical research and actual clinical treatment is becoming more and more important. Treatment cycle and administration time are two key factors in cancer chemotherapy. In order to meet clinical practice, this paper proposes an improved optimal drug scheduling model for cancer chemotherapy with a shorter treatment cycle than in previous studies. Besides, an improved optimization method of time scaling-based control variable parameterization (CVP) is applied, and the anticancer drug is administered at equal time intervals, so as to match the actual clinical treatment. The homologous simulation experiments are implemented to validate the availability of the improved model and solution method. The simulation results display that the improved model can achieve the goal closer to the actual clinical treatment, and the results are better than those of previous studies.